Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka untuk Mengakomodasi Keberagaman Karakteristik Siswa Sekolah Dasar - Grace Shinta Simbolon; Monica Sola Gratia Panjaitan; Riska N Br Sitepu; Marie N Simorangkir; Putri Pakpahan; Asna Istikmalatul Muktamaroh (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to analyze the implementation of differentiated learning in the Merdeka Curriculum to accommodate students’ characteristics in elementary schools. The research employed a qualitative approach using the Systematic Literature Review (SLR) method. Data sources were obtained from national and international journal articles accessed through Google Scholar, Garuda, and ScienceDirect published between 2016–2026. Data collection was conducted through documentation techniques and analyzed using descriptive qualitative analysis. The findings indicate that differentiated learning helps teachers adjust learning content, processes, and products based on students’ readiness, interests, and learning profiles. The implementation of differentiated learning also improves students’ motivation, engagement, critical thinking skills, creativity, and learning outcomes in elementary schools. However, its implementation still faces several challenges, including limited teacher understanding, lack of professional training, limited time, and difficulties in managing heterogeneous classrooms. Therefore, improving teacher competence, providing adequate facilities and infrastructure, and supporting educational policies are necessary to optimize the implementation of differentiated learning in the Merdeka Curriculum.